(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Premessa - 2. Metodo concertativo, bilateralità e laicità - Paesi diversi, bilanciamenti simili. Concertative method and balancing techniques in the legal discipline of religious freedom in times of emergency (about the reports by Silvia Baldassarre, Simone Gianello and Paolo Zicchittu) ABSTRACT: In this contribution, which takes its cue from the reports by Silvia Baldassarre, Simone Gianello and Paolo Zicchittu, the author makes some brief considerations about the method followed - and the balancing results achieved - by the political decision-maker in the emergency management of religious freedom.